Atypical Rulings of the Indonesian Constitutional Court - Bisariyadi Bisariyadi (Hasanuddin Law Review, 2016)
In deciding judicial review cases, the Court may issue rulings that is not in accordance to what is stipulated in the Constitutional Court Law (Law Number 8 Year 2011). Atypical rulings means that the court may reconstruct a provision, delay the legislation/rulings enactment or give instruction to lawmakers. In addition, the court also introduce the “conditionally (un)constitutional” concept. This essay attempts to identify and classify these atypical rulings, including conditionally (un) constitutional rulings, by examined the constitutional court judicial review rulings from 2003 to 2015. This study will provide a ground work for advance research on typical rulings by the Indonesian constitutional court.